THE EFFECT OF SERVICE QUALITY AND PRICE ON CONSUMER SATISFACTION AT J&T CARGO BRANCH SUB B PETEMON SURABAYA - Zumrotul Khoiriyah; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2025)
This study investigates